Comparative analysis of varimax and Promax rotation methods in exploratory factor analysis - Ahmed, Abdalla; Maruod, Walla (Edelweiss Applied Science and Technology, 2025)
This study compares two widely used rotation techniques in exploratory factor analysis (EFA): Varimax, an orthogonal method, and Promax, an oblique method. Sample data from 394 students were analyzed using JASP software to evaluate the two methods. Both rotations identified latent constructs influencing academic achievement after factor extraction via principal axis factoring. Although both methods retained the same number of factors, the pattern and magnitude of variable loadings differed. The Kaiser-Meyer-Olkin (KMO) test indicated superior reliability for Promax, which achieved significantly higher sampling adequacy (MSA = 0.882) compared to Varimax (MSA = 0.500). Bartlett’s test confirmed the suitability of factor analysis by revealing significant interrelationships among variables (p < 0.001). Promax results were easier to interpret, revealing moderately positive inter-factor correlations and explaining 59% of the cumulative variance, compared to 56% for Varimax. Conversely, Varimax produced uncorrelated factors, ideal when factor independence is desired. Parallel analysis supported the retention of three factors for both methods. Path diagrams further illustrated Promax’s performance in capturing related constructs. Overall, the findings suggest that Promax outperforms Varimax in handling interrelated constructs, offering higher reliability and accounting for a greater proportion of variance. In contrast, Varimax, based on the assumption of factor independence, provides a clearer but less nuanced interpretation.